Policy rules for capital controls - Gurnain Kaur Pasricha (Bank of Canada, 2017)
This paper attempts to borrow the tradition of estimating policy reaction functions in monetary policy literature and apply it to capital controls policy literature. Using a novel weekly dataset on capital controls policy actions in 21 emerging economies over the period 1 January 2001 to 31 December 2015, I examine the mercantilist and macroprudential motivations for capital control policies. I introduce a new proxy for mercantilist motivations: the weighted appreciation of an emerging-market currency against its top five trade competitors. There is clear evidence that past emerging-market policy systematically responds to both mercantilist and macroprudential motivations. The choice of instruments is also systematic: policy-makers respond to mercantilist concerns by using both instruments - inflow tightening and outflow easing. They use only inflow tightening in response to macroprudential concerns. I also find that policy is acyclical to foreign debt but is countercyclical to domestic bank credit to the private non-financial sector. The adoption of explicit financial stability mandates by central banks or the creation of inter-agency financial stability councils increased the weight of macroprudential factors in the use of capital controls policies. Countries with higher exchange rate pass-through to export prices are more responsive to mercantilist concerns.
Keywords: F3; F4; F5; G0; G1; 330; International topics; Financial system regulation and policies; Financial stability; Exchange rate regimes